2007
DOI: 10.1016/j.cmet.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Causes Severe but Reversible Leptin Resistance in Arcuate Melanocortin Neurons

Abstract: Despite high leptin levels, most obese humans and rodents lack responsiveness to its appetite-suppressing effects. We demonstrate that leptin modulates NPY/AgRP and alpha-MSH secretion from the ARH of lean mice. High-fat diet-induced obese (DIO) mice have normal ObRb levels and increased SOCS-3 levels, but leptin fails to modulate peptide secretion and any element of the leptin signaling cascade. Despite this leptin resistance, the melanocortin system downstream of the ARH in DIO mice is over-responsive to mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
412
3
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 497 publications
(472 citation statements)
references
References 56 publications
41
412
3
16
Order By: Relevance
“…Although this model does not lead to total loss of Ift88, it eliminates confounding effects of cilia loss during development, an advantage that the previously used POMC-Cre transgene does not possess (23,35). It was previously shown that other obese leptinresistant animals regain leptin sensitivity on regulation of body composition through controlled feeding (36,37). Furthermore, the study presented here allowed for the repetitive assessment of leptin sensitivity in the same cohort of mice at different adiposity and leptin levels.…”
Section: Discussionmentioning
confidence: 93%
“…Although this model does not lead to total loss of Ift88, it eliminates confounding effects of cilia loss during development, an advantage that the previously used POMC-Cre transgene does not possess (23,35). It was previously shown that other obese leptinresistant animals regain leptin sensitivity on regulation of body composition through controlled feeding (36,37). Furthermore, the study presented here allowed for the repetitive assessment of leptin sensitivity in the same cohort of mice at different adiposity and leptin levels.…”
Section: Discussionmentioning
confidence: 93%
“…High fat feeding can affect a variety of brain and peripheral pathways involved in energy balance [25,26] including beta adrenergic function [21]. Furthermore, these effects are dependent upon genetic vulnerability to diet-induced obesity and are correlated with lipid and glucose metabolism [39,46].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has extensive experience and expertise in using a male mouse model for acute glycemic control studies (Enriori et al, 2007). We further tested the acute effects of ZNS on blood glucose using male C57BL/6J mice (5 animals per treatment group 2 h post drug treatment) via saphenous vein bleeds in order to investigate the mechanism of the effect of ZNS treatment on OLZ-associated glucose dysregulation and to determine to what extent increased blood glucose was weight-related.…”
Section: Drug Treatmentfblood Glucosementioning
confidence: 99%